Global analysis of the dynamics of a mathematical model to intermittent HIV treatment - Carvalho, Tiago de; Cristiano, Rony; Goncalves, Luiz Fernando [UNESP]; Tonon, Durval Jose (Springer, 2020)
The aim of this paper is to study the qualitative dynamics of a piecewise smooth system modeling the intermittent treatment of the human immunodeficiency virus. Typical singularities and closed orbits are observable, and we quantitatively explore the dynamics around those singularities and closed orbits. Moreover, we conclude that this protocol always will be successful since the trajectory passing through any initial condition converges to one of these distinguished orbits. Our formal mathematical results corroborate the real-world observation, where the virus is not eliminated, but the number of infected cells is controlled around a specific value.
Keywords: HIV; Piecewise smooth vector fields; Typical singularities; Basin of attraction; Crossing limit cycle